"Side-stepping maneuver": not the more efficient technique to change direction amongst young elite soccer players - Rouissi, M.; Chtara, M.; Owen, A.; Chaalali, A.; Chaouachi, A.; Gabbett, T.; Chamri, K. (International Journal of Performance Analysis in Sport, 2015)
Two change of direction (COD) maneuvers (Side-Stepping [SS] and Crossover-Stepping [CS]) are often described in the scientific literature. However, there are other COD techniques which have not been investigated. Therefore, the main aim of this study was to compare the performance of SS maneuver and a "By-Pass" (BP) COD maneuver (multiple short steps to avoid reduction in running speed by performing longer distance and wider angle of COD compared to SS) over several angles of COD. Seventy-three male soccer players (from U15 and U18 categories) competing at youth level participated in the study. Each age-category was divided into Starters Players (SP) and Non-Starters Players (NSP). Players performed a total of 26 sprints of 10-m, either in straight-line or with a COD (5 m straight ahead and the other 5 m with a turn of 45°, 90°, and 135°) using the two different maneuvers separately: SS and BP. Sprint performance was significantly better at 45°, 90° and 135° CODs (p<0.001) when players performed a BP maneuver compared to SS. Significant age-group effects were revealed, with U18 players demonstrating better performances (p<0.001) than U15 players in all COD angles. Further analysis revealed a significant effect of playinglevel, with SP having better performances (p<0.002) compared to NSP in all COD angles. It can be concluded that the BP is a more effective maneuver than SS for changing direction in youth elite soccer players. Also, COD tests with angles ranging between 45° and 135° discriminate between Starters and Non-starters in youth soccer.